Participatory Leadership as a Strategic Determinant of Teacher Performance in Value-based Elementary Schools - Julia Hutabarat; Lia Yuliana (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2026)
The low quality of education in Indonesia, as reflected in PISA 2022 and National Assessment 2024 results, indicates structural problems in classroom learning processes, particularly related to teacher performance and principal leadership. This study aims to analyze the effect of principals' participative leadership on teacher performance in value-based elementary schools implementing the Reflective Pedagogy Paradigm. A quantitative ex-post facto design was employed. The study involved 74 teachers selected through a total sampling technique from seven elementary schools. Data were collected using a Likert-scale questionnaire that had been validated through expert judgment and empirical testing, with reliability coefficients of 0.912 for participative leadership and 0.894 for teacher performance. The data were analyzed using simple linear regression with robust standard error estimation (HC3) to correct for heteroscedasticity. The results indicate that participative leadership has a positive and significant effect on teacher performance (β = 0.776, p < .001), explaining 59.7% of the variance in performance outcomes (Adjusted R² = 0.597). Teacher involvement in decision-making, dialogic communication, and professional empowerment were found to enhance overall performance. The study concludes that optimizing participative leadership is a strategic factor in improving teacher performance. The implication is that principal development programs should integrate value-based leadership training to foster professional empowerment and collaborative school culture.